Slackline Training: an innovative intervention for improving balance and physical fitness in older adults (Research, Society and Development, 2021)
This experimental study investigated the effects of slackline training on the balance and physical fitness of elderly individuals. Participants in a university extension program were divided into two groups: a slackline training group (n = 7, 73.14 ± 6.38 years) and a control balance training group (n = 7, 78.71 ± 5.56 years). The study variables were muscle strength (MS), flexibility (FLEX), static balance (SB), dynamic balance (DB), self-selected walking speed (WS), maximal walking speed (VMAX). Data were analyzed using generalized estimating equations, effect sizes, and Spearman’s correlation coefficients. MS, FLEX, DB, WS, and VMAX improved significantly in the slackline group after the intervention. Post-test MS and WS differed significantly between slackline and control balance training groups. There was a strong association between pre-and post-test DB, MS, FLEX, and VMAX. Slackline balance training proved to be a motivating and challenging method for improving the physical fitness of the elderly.